2012
DOI: 10.1021/mz300065t
|View full text |Cite
|
Sign up to set email alerts
|

Naphthodithiophene-Based Donor–Acceptor Polymers: Versatile Semiconductors for OFETs and OPVs

Abstract: We report the synthesis, characterization, and OFET and OPV properties of a series of novel naphthodithiophene (NDT3)-based donor− acceptor semiconducting polymers. A striking feature of the present polymers is the very close π−π stacking of 3.5 Å, most likely as a result of the large π system and the D−A system in the polymer backbone. PNDT3NTz-DT, in particular, is found to be one of the few examples of versatile polymers that exhibit both the field-effect mobility of ∼0.5 cm 2 /(V s) and the PCE of ∼5%. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 34 publications
3
99
1
Order By: Relevance
“…In particular, for semiconducting polymers with donor-acceptor backbones that have strong intermolecular interactions, branched alkyl groups are necessary for solubility in organic solvents. 19,20 Although such bulky branched alkyl groups efficiently increase the solubility, they suppress the aggregation or close interchain π-π stacking of the polymers relative to the linear alkyl groups, resulting in inefficient charge transport. 20 A recent study demonstrated that moving the branching position in the branched alkyl group away from the conjugated backbone reduced the steric effect and π-π stacking distances, which enhanced the charge carrier mobilities in OFET devices.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, for semiconducting polymers with donor-acceptor backbones that have strong intermolecular interactions, branched alkyl groups are necessary for solubility in organic solvents. 19,20 Although such bulky branched alkyl groups efficiently increase the solubility, they suppress the aggregation or close interchain π-π stacking of the polymers relative to the linear alkyl groups, resulting in inefficient charge transport. 20 A recent study demonstrated that moving the branching position in the branched alkyl group away from the conjugated backbone reduced the steric effect and π-π stacking distances, which enhanced the charge carrier mobilities in OFET devices.…”
Section: Introductionmentioning
confidence: 99%
“…Benzothiadiazole (BTz) and naphthobisthiadiazole (NTz), a doubly BTz-fused heteroaromatic ring, are chosen as the acceptor units to create two polymer semiconductors M9 and M10 (Figure 4), respectively. Polymers were synthesized under Stille coupling and show good solubilities in common organic solvents when appropriate side chains were used on the bridging thiophene units [81]. Using naphthobisthiadiazole as acceptor unit, the polymer M10 shows broader absorption and red-shifted λmax of 632 nm compared to the benzothiadiazole-based polymer analogue M9.…”
Section: Naphtho[23-b:67-b′] Dithiophene-based Organic Semiconductorsmentioning
confidence: 99%
“…P41 exhibits not only high field-effect transistor (FET) mobility of about 0.56 cm 2 /Vs, but also a high PCE of 6.3 %, both of which are significantly higher than that of the BT-based analogues [53]. Combined naphthodithiophenes with NT, polymer P42 including highly π-extended (four-ring fused) heteroarenes both as the donor and acceptor units were synthesized by Osaka et al By virtue of this large π-extended system, a very close π-π stacking of 3.5 Å showed up in the solid state and it was found to be one of the few examples of versatile polymers that exhibit both high FET mobility of ~0.5 cm/ Vs and high PCE of ~5 % [54]. However, due to the highly π-extended system along the backbone, the Achilles' heel of P42 is its low solubility, which will severely hinder its processability.…”
Section: Nt-based Donor Polymers For Photovoltaic Applicationmentioning
confidence: 99%